2016
DOI: 10.1073/pnas.1609502113
|View full text |Cite
|
Sign up to set email alerts
|

GIV/Girdin activates Gαi and inhibits Gαs via the same motif

Abstract: We previously showed that guanine nucleotide-binding (G) protein α subunit (Gα)-interacting vesicle-associated protein (GIV), a guanine-nucleotide exchange factor (GEF), transactivates Gα activity-inhibiting polypeptide 1 (Gαi) proteins in response to growth factors, such as EGF, using a short C-terminal motif. Subsequent work demonstrated that GIV also binds Gαs and that inactive Gαs promotes maturation of endosomes and shuts down mitogenic MAPK–ERK1/2 signals from endosomes. However, the mechanism and conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 39 publications
(90 reference statements)
4
60
0
Order By: Relevance
“…Findings also reveal how deregulation of this pathway fuels the growth of tumor cells under energetic stress.
10.7554/eLife.20795.002Figure 1.AMPK binds and phosphorylates GIV at Ser ( S ) 245.( A ) Schematic showing the functional modules of the multimodular signal transducer GIV. From the N- to the C-terminus the domains are-- a Hook-domain (grey) which binds microtubules (Simpson et al, 2005); a long coiled-coil domain (green) assists in homo/oligomerization (Enomoto et al, 2005); a Gα-binding domain (GBD; yellow) which constitutively binds Gαi/s proteins (Le-Niculescu et al, 2005); a PI(4)P-binding motif (pink) which enables GIV to bind PI4P-enriched membranes at the Golgi and the PM (Enomoto et al, 2005); an evolutionarily conserved GEF motif (red) which binds and activates Gαi (Garcia-Marcos et al, 2009) and inactivates Gαs (Gupta et al, 2016), and releases ‘free’ Gβγ from both. The C-terminal ~200 aa of GIV (purple) also has key domains that enable GIV to bind and remodel actin (Enomoto et al, 2005), bind and enhance phosphorylation of Akt (Anai et al, 2005; Enomoto et al, 2005), bind ligand-activated RTKs (Ghosh et al, 2010; Lin et al, 2014), and bind and activate Class 1 PI3-Kinases (Lin et al, 2011).
…”
Section: Introductionmentioning
confidence: 99%
“…Findings also reveal how deregulation of this pathway fuels the growth of tumor cells under energetic stress.
10.7554/eLife.20795.002Figure 1.AMPK binds and phosphorylates GIV at Ser ( S ) 245.( A ) Schematic showing the functional modules of the multimodular signal transducer GIV. From the N- to the C-terminus the domains are-- a Hook-domain (grey) which binds microtubules (Simpson et al, 2005); a long coiled-coil domain (green) assists in homo/oligomerization (Enomoto et al, 2005); a Gα-binding domain (GBD; yellow) which constitutively binds Gαi/s proteins (Le-Niculescu et al, 2005); a PI(4)P-binding motif (pink) which enables GIV to bind PI4P-enriched membranes at the Golgi and the PM (Enomoto et al, 2005); an evolutionarily conserved GEF motif (red) which binds and activates Gαi (Garcia-Marcos et al, 2009) and inactivates Gαs (Gupta et al, 2016), and releases ‘free’ Gβγ from both. The C-terminal ~200 aa of GIV (purple) also has key domains that enable GIV to bind and remodel actin (Enomoto et al, 2005), bind and enhance phosphorylation of Akt (Anai et al, 2005; Enomoto et al, 2005), bind ligand-activated RTKs (Ghosh et al, 2010; Lin et al, 2014), and bind and activate Class 1 PI3-Kinases (Lin et al, 2011).
…”
Section: Introductionmentioning
confidence: 99%
“…Gupta V., et al, 15 also revealed how the pleiotropic GEF/ GDI functions of GEMs may be controlled by post-translational modifications. They showed that in the case of the prototypical GEM GIV, sequential phosphorylation of 2 Ser residues that flank the bifunctional GEF/GDI motif on GIV by 2 kinases, CDK5 35 and PKCu, 36 ensures that GIV exerts its GEF and GDI activities on Gai and Gas, respectively, in a temporally and spatially segregated manner (Fig.…”
mentioning
confidence: 99%
“…15 The members of this family share very little sequence homology and act within diverse signaling cascades; what unites them is the ability to couple activation of these cascades to G protein signaling (Fig. 1) via an evolutionarily conserved motif of »30 aa that directly binds to G proteins.…”
mentioning
confidence: 99%
See 2 more Smart Citations